Islamic Counseling Using the Sirah Shahabiyah Method to Enhance Female Students' Spirituality - Fitria, Almah (Institut Agama Islam Negeri Parepare, 2025)
This study aims to analyze the effectiveness of the Sirah Shahabiyah method in enhancing the spirituality of female students at MTs. Ar-Rahman Kaju, Bone Regency. Sirah Shahabiyah is an approach based on inspirational stories of female companions of the Prophet, which carry spiritual values, piety, and courage in defending Islam. This study employs a pre-experimental design with a one-group pretest-posttest approach, involving 25 students as samples. The results show that this method significantly improves students' spirituality, as evidenced by the significance value (0.00) < 0.05 using SPSS statistical tests. These findings confirm that storytelling techniques based on Sirah Shahabiyah can serve as an effective alternative in Islamic counseling in educational environments.